2015
DOI: 10.1111/jbi.12501
|View full text |Cite
|
Sign up to set email alerts
|

Geographical patterns of butterfly species diversity in the subtropical Ryukyu Islands: the importance of a unidirectional filter between two source islands

Abstract: Aim To examine the roles of geohistorical and ecological factors in the development of butterfly assemblages on continental islands with multiple source pools.Location The Ryukyu Islands, Japan. This arc of continental islands is located between two source islands, Kyushu and Taiwan, and contains two major straits, the Tokara and Kerama gaps.Methods A total of 489 butterfly species were identified on 59 islands, including the two source islands. The influences on species richness and rarity of latitude, area, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…We found that 94% of the global datasets on island systems that we screened had a high (> 0.5) contribution of species replacement to multiple‐island dissimilarity, indicating that species turnover generally dominates beta diversity across various biological groups. For example, extreme contributions of species replacement to multiple‐island dissimilarity were found in island butterflies in Lake Kenyir, Malaysia (Yong et al ., ) and the Ryukyu Island, Japan (Hirao et al ., ). One explanation for these patterns of predominant turnover could be sampling effects, which can be a potential explanation for at least some variance in turnover between islands in most biogeographical studies, particularly as the Simpson index is sensitive to a large number of zero values (Dapporto et al ., , ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We found that 94% of the global datasets on island systems that we screened had a high (> 0.5) contribution of species replacement to multiple‐island dissimilarity, indicating that species turnover generally dominates beta diversity across various biological groups. For example, extreme contributions of species replacement to multiple‐island dissimilarity were found in island butterflies in Lake Kenyir, Malaysia (Yong et al ., ) and the Ryukyu Island, Japan (Hirao et al ., ). One explanation for these patterns of predominant turnover could be sampling effects, which can be a potential explanation for at least some variance in turnover between islands in most biogeographical studies, particularly as the Simpson index is sensitive to a large number of zero values (Dapporto et al ., , ).…”
Section: Discussionmentioning
confidence: 97%
“…Studies in insular biogeography that assess the contributions of the various groups of factors in determining compositional dissimilarities may be confounded by joint effects of geological age, historical events, multiple source pools, climate and human disturbance (Fattorini, ; Dennis et al ., ; Hirao et al ., ). The natural laboratories created by hydroelectric damming, such as the Thousand Island Lake in eastern China, can tease these factors apart (Benchimol & Peres, ; Wilson et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A broad range of latitudinal (22°N to 45°N) and altitudinal (0–3,776 m) gradients across these archipelagos create diverse climatic conditions, including subtropical, temperate and hemiboreal zones. During the Pliocene and the Pleistocene, geological processes intermittently divided the islands or periodically connected islands through land‐bridge corridors (Hirao, Kubota, & Murakami, ). These climatic and geographical conditions have resulted in a region‐specific endemic flora (Kubota, Kusumoto, Shiono, & Tanaka, ; Kubota et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Several biogeographical drivers, such as area and distance from mainland and/or other islands, have been shown to exert a direct effect on species richness as well as on compositional dissimilarity patterns in archipelagos (Guerrero et al ., ; Hausdorf & Hennig, ; Fattorini, ,b, ,b; Pitta et al ., , ; Cabral et al ., ; Carvalho & Cardoso, ). Also palaeogeographic history, reflected in current inter‐island distances/connections, and distances from the mainland or possible connection intervals during past geological time periods is expected to be most influential on compositional dissimilarity patterns in continental archipelagos (Hausdorf & Hennig, ; Fattorini, ,b, ; Hirao et al ., ). Recently, it has been shown that palaeogeographic history, i.e.…”
Section: Introductionmentioning
confidence: 97%